Systematical and Biochronological review of Plio-Pleistocene Alceini (Cervidae; Mammalia) from Eurasia - BREDA, Marzia; MARCHETTI, Marco (Quaternary Science Reviews, 2005)
Systematics, taxonomy and phylogeny ofEurasian fossil moose are discussed in order to analyse their distribution in space and time. The largest European collections were studied. We recognise the genus Cervalces, including the chronospecies C. gallicus, C. carnutorum and C. latifrons, as well as the genus Alces, with the species A. alces. Cervalces differs from Alces in the facial area, in the length ofthe antlers and in the orientation of the palmation. Taking into account as more bibliography as possible, we suggest that the Siberian remains, due to their distance from the type localities, have size ranges and beam proportions a little different from the coeval European ones, so they are regarded as different geographic populations. Cervalces latifrons postremus systematics and chronology have been reconsidered. It results that it was present only in Siberia during the penultimate glaciation and was ofthe same body size as typical C. latifrons. It is likely that A. alces is not the direct descendant ofthe last European Cervalces, but its origin is still an open question. The present analysis provides a clearer picture ofthe geographical and chronological distribution of Cervalces and Alces.